An evaluation of European initiatives established to encourage industry‐led development of selective fishing gears. (5th August 2019) - Feekings, Jordan; O'Neill, Finbarr G.; Krag, Ludvig; Ulrich, Clara; Veiga Malta, Tiago
Abstract: There are numerous examples from across Europe where collaborative science‐industry initiatives, which provide a bottom‐up approach to trawl gear development, have been successful in developing selective gears. For fishers, the collaborative approach creates a sense of ownership and control over the gears developed and often a greater desire for them to achieve their objectives. Despite the many benefits of collaborative initiatives, a lack of clarity and transparency, incorrect incentives, unclear communication, and distrust or diverging perceptions can inhibit their performance. The present review examines the different collaborative approaches to fishing gear development that have been established within Europe, highlighting their salient features, comparing their objectives, and discussing the types and effectiveness of the incentives offered. Also examined is how the reform of the European Union's (EU) Common Fisheries Policy (CFP), together with the proposed reform of the technical measures framework, can potentially improve the flexibility in the technical regulations and allow for such initiatives to be a central part in improving the state of fish stocks throughout the EU. Finally, a framework is proposed on how initiatives pertaining to industry‐led fishing gear development might look like under the reformed CFP.